A combined factorial experiment and heuristic search for simulation optimization - Loh, Yoon Loong. (2009)
Simulation provides a means to determine the output performance measures for different sets of input parameters. While it is an effective tool for analyzing manufacturing systems, it relies entirely on the system designer to decide what changes are needed in the input parameters to achieve better results. This drawback can be overcome by appending appropriate optimization algorithms to the simulation model to perform the decision making task. The main objective of this research work is to develop an effective and efficient methodology to couple simulation with optimization techniques.